Is the natural rate of growth exogenous? - Miguel Leon-Ledesma; Anthony P. Thirlwall (PSL Quarterly Review, 2000)
In mainstream growth theory, including endogenous growth theory, the naturalrate of growth as defined by Harrod, is still treated as exogenous. In practice, however, both the growth of the labour force and the growth of labour productivity are endogenous to demand. This has theoretical implications for the adjustment process between the actual, warranted and natural growth rates. It also has serious implications for the way in which the growth process is viewed: whether from the supply side or demand side. It is shown for a sample of 15 OECD countries 1961-1995 that the natural rate of growth has been very responsive to the actual growth rate, and it is argued that for most countries demand constraints operate long before supply capacity is reached.